Effect of caffeine contained in a cup of coffee on microvascular function in healthy subjects - Katsuhiko Noguchi; Toshihiro Matsuzaki; Mayuko Sakanashi; Naobumi Hamadate; Taro Uchida; Mika Kina-Tanada; Haruaki Kubota; Junko Nakasone; Matao Sakanashi; Shinichiro Ueda; Hiroaki Masuzaki; Shogo Ishiuchi; et al. (Elsevier, 2015)
Recent epidemiological studies have demonstrated that coffee drinking is associated with reduced mortality of cardiovascular disease. However, its precise mechanisms remain to be clarified. In this study, we examined whether single ingestion of caffeine contained in a cup of coffee improves microvascular function in healthy subjects. A double-blind, placebo-controlled, crossover study was performed in 27 healthy volunteers. A cup of either caffeinated or decaffeinated coffee was drunk by the subjects, and reactive hyperemia of finger blood flow was assessed by laser Doppler flowmetry. In an interval of more than 2 days, the same experimental protocol was repeated with another coffee in a crossover manner. Caffeinated coffee intake slightly but significantly elevated blood pressure and decreased finger blood flow as compared with decaffeinated coffee intake. There was no significant difference in heart rate between caffeinated and decaffeinated coffee intake. Importantly, caffeinated coffee intake significantly enhanced post-occlusive reactive hyperemia of finger blood flow, an index of microvascular endothelial function, compared with decaffeinated coffee intake. These results provide the first evidence that caffeine contained in a cup of coffee enhances microvascular function in healthy individuals.